Feeding intolerance in critically ill patients with Covid-19 - Marek Nalos (Indonesian Nutrition Association, 2022)
Approximately 0.5-1% of patients with COVID-19 develop respiratory failure, shock or multi-organ failure requiring intensive care unit admission. COVID-19 pneumonia is characterised by high fevers, increased energy utilisation and skeletal muscle catabolism. The delta variant has direct gastrointestinal effects resulting in diarrhoea, nausea, and vomiting. Combined these rapidly impair nutritional status. It is therefore important to quickly identify factors leading to feeding intolerance and manage them with a sense of urgency to prevent malnutrition during critical illness.